Production analysis applied to work improvement - J.R. Broomfield; Andrew Price; Francis C. Harris (1984)
This Note provides and introduction to the research being carried out in the Department of Civil Engineering at Loughborough University and funded by the Science and Engineering Research Council (SERC) into Work Study applied to construction work. The emphasis is directed towards ascertaining site efficiency factors and the methods of determining operation times. In subsequent notes the measuring techniques will be explained in detail and examples of typical data for us in estimating and cost control described.